AICCRA Field Trip Guide Zambia - International Water Management Institute (Accelerating Impacts of CGIAR Climate Research for Africa, 2025)
This field trip offers an opportunity to witness how climate services and bundled innovations for climate-smart agriculture are being deployed to strengthen the resilience of smallholder farming systems. Participants will visit two demonstration sites, each showcasing distinct approaches to climate adaptation and agricultural transformation in action.